Radiação ultravioleta e o ensino de biologia: utilizando o arduino como recurso didático - Duarte, Igor Alberto (Universidade Federal de São Carlos, 2024)
This project aims to contribute to the teaching of Science by seeking to relate concepts from Physics and Biology. It utilizes Arduino, a technological device, as a didactic resource in the classroom, thus surpassing traditional methodology and fostering enhanced learning among students. When exposed to sunlight, the device measures the degree of ultraviolet radiation and the brightness emanating from the sun, generating results that can be analyzed and discussed with students later on. The proposed experiment has proven to be effective, providing data that can create context for teaching about the biological implications of ultraviolet radiation, having been shown to elementary school students, where they were able to see the device working.
Ultraviolet Radiation and the Teaching of Biology: Utilizing Arduino as a Didactic Resource
Keywords: Ensino de biologia; Radiação ultravioleta; Tecnologias da informação e comunicação aplicadas ao ensino.; Biology teaching; Ultraviolet radiation; Information and communication technologies applied to teaching; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO